1989
DOI: 10.1016/0014-5793(89)81384-5
|View full text |Cite
|
Sign up to set email alerts
|

Variations in genome fragments coding for RNA polymerase in human and simian hepatitis A viruses

Abstract: The genome of hepatitis A virus (HAV) isolated from spontaneously infected African vervet monkey (Cercopithecus aerhiops) has been cloned and partially sequenced. Comparison of genome fragments (1248 and 162 bp) from the 3D (RNA polymerase) region with the corresponding parts of human HAV genomes revealed a high degree of heterogeneity: there were altogether 257 nucleotide changes leading to 44 substitutions in predicted amino acid sequence, i.e. 89% amino acid identity. This divergence is considered to be sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Genomic sequence analysis of simian hepatitis A virus strains isolated from naturally infected owl [12], cynomolgus [13] or African green monkey [14] revealed that these strains differ greatly from human HAV as well as between each other. In the present study we have provided evidence for natural infection of rhesus monkeys with HEV.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic sequence analysis of simian hepatitis A virus strains isolated from naturally infected owl [12], cynomolgus [13] or African green monkey [14] revealed that these strains differ greatly from human HAV as well as between each other. In the present study we have provided evidence for natural infection of rhesus monkeys with HEV.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing of the virus from Asian and African monkeys revealed that these viruses were genetically distinct from known human HAV strains (Fig. 1) [30–32]. In addition, these studies confirmed that amino acid changes within the immunodominant neutralization epitope [33–35] were responsible for the altered antigenicity and host range.…”
Section: Hepatitis a Virus – Nonhuman Primate Infectionsmentioning
confidence: 78%
“…Variability in 3D polymerase region has been described for human HAV strains; 12–14 human and simian HAVs, 15 and more recently among human HAV genotypes 16 . With the availability of nucleotide sequences of Nor21 strain, representing subgenotype IIIA from GenBank in November 2002, 3D polymerase region of HAV IIIA strains examined in this study was identified.…”
Section: Discussionmentioning
confidence: 99%
“…The dendrogram based on the alignment of RNA polymerase region (116 bp) of 31 specimens and other strains of HAV is shown in Figure 2. Comparison of cluster 1 strains (15) in the equivalent genomic region of HM175 and other strains of IB showed PNI 98.8 ± 0.88 and 99.4 ± 0.3, respectively. PNI within the strains of cluster 1 is 99.4 ± 0.3.…”
Section: Genotyping and Nucleotide And Amino Acid Sequence Analyses Omentioning
confidence: 95%
See 1 more Smart Citation